Petunjuk Nabi SAW dalam Menjaga Kesehatan - Nursalim, Danni; Muhammad Zuldin; Aep Kusnawan; Yusuf Zainal Abidin (Jurnal Ilmu Sosial dan Humaniora, 2025)
Health is a very important asset for every person. Maintaining health is a matter that has always received attention from the vast majority of humanity throughout all times, whether at the individual, community, or even national level. Islam, as a religion that encompasses all aspects of human life, also pays attention to the health of its followers. This is because health is one of the things that will facilitate the smooth performance of worship by a servant of God. In fact, in several acts of worship, a person who is less healthy will receive concessions (rukhṣah) to not perform worship, or to substitute their worship with a way that is lighter for them. The Hadiths of Prophet Muhammad SAW, as the second source of Islamic teachings, contain numerous narratives that serve as guidance for Muslims to maintain their health. This is evidenced by the existence of a special chapter entitled Kitāb Aṭ-Ṭibb (Book of Health/Medicine), which contains matters related to disease, health, and methods of treatment. This research aims to analyze the scientific compatibility and practical relevance of health principles in Islam with the principles of modern public health. The research method uses a systematic literature review approach through searching and analyzing more than articles from national and international research journals in various languages. The author chose this approach because the object of study is hadith texts along with their explanations, which are compared with the latest research related to theory and practice of health in the modern era. The research results show that the principles of Aṭ-Ṭibb An-Nabawi (Prophetic Medicine) have high scientific validity through several controlled trials for various Islamic health practices. The framework based on maqāṣid asy-syarī'ah (objectives of Islamic law) shows perfect alignment with the Sustainable Development Goals, with implementation that requires standardization of guidelines and interdisciplinary collaboration. In conclusion, systematic integration between prophetic medicine and evidence-based medicine can optimize health standards and contribute significantly to global health security, particularly in Muslim-majority countries.